Prevalence of soil-transmitted helminths after mass albendazole administration in an indigenous community of the Manu jungle in Peru. (June 2014) - Cabada, Miguel M.; Lopez, Martha; Arque, Eulogia; Clinton White, A.
Abstract : Few data are available on the epidemiology of soil-transmitted helminths (STHs) in indigenous populations of the Peruvian Amazon. While albendazole is being increasingly used in deworming campaigns, few data exist on the impact of mass drug administration in isolated populations. We studied the prevalence of STHs, anemia, and malnutrition in a Matsigenka ethnic group from the Peruvian Amazon. Participants had received two doses of albendazole on consecutive days, 3 months before and again 2 weeks before data collection. Overall, 290 subjects were included. Most were female (53·7%) and 63·9% were ≤19 years old. Half of the participants had helminth infections. Trichiuris (30·2%), hookworm (19·1%), Ascaris (17·7%), and Strongyloides (5·6%) were the most common helminths. Other helminth ova included Capillaria hepatica and Fasciola -like eggs. Subjects of 5–19 years (51·8 %) and 20–35 years (68·6 %) old had helminths more often than those under 5 years (38%) and older than 35 years (41·5%) ( P = 0·02). Anemia was detected in 41% of children and this was more common in children under 5 years that in those of 5–19 years [odd ratio (OR) = 5·68; 95% CI: 2·71–11·88]. Overall, 72·1% of children were malnourished. Stunting was common in children (70·7%), but wasting was not (2·9%). Despite repeated albendazole administration, this population continued to have a high prevalence of STHs, anemia, and malnutrition. In addition, we detected unusual organisms and organisms that do not respond to albendazole. Further studies are needed to assess the rationale and efficacy of mass chemotherapy for STHs in the Amazon.